노화예방을 위한 운동과 마이오카인의 역할 - 안나영; 김기진 (The Asian journal of kinesiology, 2017)
[PURPOSE] This study reviewed the current trend of the importance of exercise training-related myokine's function for the prevention of aging. [METHODS] On the basis of searching on the recent research results in pubmed and the other internet research file, we reviewed the recent research output. [RESULTS] Myokine has been regarded an important factor of exercise training and brain growth factor for the prevention of Alzheimier's disease. During exercise the release of anti-inflammatory myokine from contracting skeletal muscle controled the metabolic response, and myostatin, IL-4, IL-6, IL-10, and IL-15 controled skeletal muscle hypertrophy and myogenesis. BDNF and IL-6 promoted the lipid metabolism through AMPK activation. IL-1Ra, IL-10 and sTNF-R inhibited TNF-α as the pro-inflammatory cytokine. IL-15 increased the releasing volume from contracting muscle, and promoted the anabolic factor of muscle growth. IL-7 and IL-8 activated the angiogenesis through the more activation of C-X-C receptor signal transmission. FNDC5/Irisin pathway activated brain cell and BDNF expression through the control of neurogenesis pathway. [CONCLUSIONS] Multiple myokines released from contracting skeletal muscle, and performed the important key factors for skeletal muscle hypertrophy. Therefore exercise training can be suggested the important intervention program for aging prevention and aging-related dysfunction through the delayed sarcopenia. We should try to elucidate the mechanism of myokine's molecular pathway and effects KCI Citation Count: 1